2011
DOI: 10.1007/s12205-011-1117-9
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of uplift capacity of suction caissons using multi expression programming

Abstract: Suction caissons have increasingly been used as foundations and anchors for deepwater offshore structures in the last decade. The increased use of suction caissons defines a serious need to develop more authentic methods for simulating their behavior. Reliable assessment of uplift capacity of caissons in cohesive soils is a critical issue facing design engineers. This paper proposes a new approach for the formulation of the uplift capacity of suction caissons using a promising variant of Genetic Programming (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Different parameters were taken for the algorithm to explore the optimal model. This was based on the values recommended by other researchers [24,28,29], as well as a number of preliminary runs. As can be seen in Table 3, 3 values were checked for the population size and number of generation.…”
Section: Mep-based Formulation For Shear Strength Of Sfrcbmentioning
confidence: 99%
See 1 more Smart Citation
“…Different parameters were taken for the algorithm to explore the optimal model. This was based on the values recommended by other researchers [24,28,29], as well as a number of preliminary runs. As can be seen in Table 3, 3 values were checked for the population size and number of generation.…”
Section: Mep-based Formulation For Shear Strength Of Sfrcbmentioning
confidence: 99%
“…Oltean and Grosan [27] showed that the advantage of MEP over other modeling techniques. There are few applications of this powerful tool in civil engineering domain [28,29]. It is worth mentioning that MEP possesses obvious advantage over traditional statistical modeling techniques because it does not need a preliminary definition of the form of the existing relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Using the numerical experiments, the MEP method has the capability to overtake similar techniques (Oltean & Grossan, ). Despite this algorithm having the prediction capability, MEP is not widely applied in engineering (Alavi et al ., ; Alavi & Gandomi, 2012; Gandomi et al ., ).…”
Section: Theorymentioning
confidence: 97%
“…Alavi et al [39] found that a hybrid computational model (coupling of GP and simulated annealing) provided a better prediction performance than GP did, by predicting the uplift capacity of suction caisson using the above database (Rahman et al [26]). Gandomi et al [40] proposed a promising variant of GP, namely Multi-Expression Programming (MEP), and proved its higher capability in prediction performance compared to ANN and FEM models. Multivariate Adaptive Regression Spline (MARS), developed by Friedman [41], is a exible regression model that ts relationships which are nearly additive and involve lesser variables.…”
Section: Introductionmentioning
confidence: 99%